“Qur’anic Cosmolinquistics in Surah Yunus (A Stylistic Study of the Arabic Language)” - Mustaqim, Mustaqim; Moh. Supriyadi, Moh. Supriyadi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2022)
Arabic is a unique language that has a very rich vocabulary, so it is very relevant that Allah created the Qur'an using Arabic so that the Qur'an has beauty both from the beauty of its lafadz (Muhasinaat al-lafdziyah), and the beauty of its meaning (Muhasinaat al-maknawiyah). Of course, the use of sentences in the Qur'an has a beautiful language style and is adjusted to the actual facts and reality. Al-Qur'an cosmolinguistics is a language study of the Qur'anic explanation of the cosmos from a stylistic point of view to see the beauty of language style both in terms of morphology and syntax. The beauty of language style in terms of morphology is the use of the sentence السماوات (sky) using the sentence jama' (many), while the sentence الارض tends to use mufrod (singular). The beauty of the syntax includes the form of the number of fi'liyah (verbal sentences), the number of ismiyah (nominal sentences) and sibhulnomor (semi-composition)